The first flight measurement with the CREAM silicon charge detector - I. H. Park; H. S. Ahn; P. Allison; M. G. Bagliesi; J. J. Beatty; BIGONGIARI, GABRIELE; P. Boyle; J. T. Childers; N. B. Conklin; S. Coutu; M. A. DuVernois; O. Ganel; et al. (Tata Inst Fundamental Research, 2005)
The Cosmic Ray Energetics And Mass (CREAM) payload had its first successful flight in December 2004 from McMurdo Station, Antarctica as a long duration balloon payload. The goal of the experiment is to obtain the experimental data to understand their source and acceleration mechanisms of high-energy cosmic-ray particles. The CREAM Silicon Charge Detector (SCD) was designed for charge identification of incident cosmic rays. The ongoing analysis of SCD flight data is discussed and preliminary results are presented.